Composite Steel Joist Analysis Using Experimental Stiffness Factor from Push-Out Tests - Yanez-Cart, S (Elsevier Ltd, 2017)
The stud anchor stiffness coefficient is vital for computing the deflections of composite steel joists (CSJ), although the way to capture this value can be challenging. A commonly used experimental method to compute this coefficient is the push-out test presented in EN-1994. However, the method does not address the incorporation of the steel metal deck currently used in the vast majority of composite decks. In order to tackle this problem, we present a modified version of the push-out experiment to better determine the stiffness coefficient when the stud anchor is placed in the weak or strong side with respect to the steel deck stiffener. Furthermore, 13 mm and 16 mm diameter studs are used in order to investigate lower capacities and to compare with the standard 19 mm diameter connector. An analytical solution of the CSJ system which incorporates the stud anchor stiffness coefficient is utilized to predict the overall system deflection when the effective composite moment of inertia of the joist is included. Results demonstrate the effectiveness of placing the stud in the strong side, and the accuracy of the enhanced push-out test. © 2017 Elsevier Ltd